1866 Mass. Acts 197 - (:unkn) unknown (My University, 1866)
An Act Concerning The Militia, § 120: A soldier who unnecessarily or without order from a superior officer comes to any parade with his musket, rifle or pistol loaded with ball, slug or shot, or so loads the same while on parade, or unnecessarily or without order form a superior officer discharges the same when going to, returning from or upon parade, shall forfeit not less than five nor more than twenty dollars.
Keywords: ARMED FORCES